Girls in pants : the third summer of the Sisterhood - Brashares, Ann. (New York : Dell Laurel-Leaf, 2007)
The Sisterhood of the Traveling Pants graduates from high school and spends their last summer before college learning about life and themselves.
6.8.
Young Adult.
Young Adult
Keywords: Best friends -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Jeans (Clothing) -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Jeans (Clothing) -- Fiction